2012
DOI: 10.1093/infdis/jis674
|View full text |Cite
|
Sign up to set email alerts
|

Use of Human Monoclonal Antibodies to Treat Chikungunya Virus Infection

Abstract: Chikungunya virus (CHIKV) is an alphavirus prevalent in tropical regions. It causes an acute febrile disease that, in elderly individuals and newborns, is often associated with severe complications. We previously reported the isolation and characterization of 2 human monoclonal antibodies neutralizing CHIKV in vitro: 5F10 and 8B10. Here, we tested their efficacy in vivo as prophylactic and therapeutic treatments of CHIKV infection in AGR129 mice. In both settings, 5F10 and 8B10 were able to significantly delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 14 publications
0
63
1
Order By: Relevance
“…In addition, natural antibodies present in the sera of uninfected C57BL/6 mice were able to partially inhibit CHIKV (75). Furthermore, therapies based on passively transferred anti-CHIKV neutralizing antibodies conferred protection to A129 mice (42,44,45,70,71,73,(76)(77)(78) and nonhuman primates (37) against CHIKV and protection to mice against more distantly related arthrogenic alphaviruses (43,93,96), establishing the key role of humoral immunity in the control of CHIKV replication. Interestingly, complete protection from CHIKV challenge can be obtained using adoptive transfer of antibodies induced by immunization with a CHIKV/IRES vaccine candidate and occurs in the absence of CD4 ϩ /CD8 ϩ T cells (42); a titer of 35 for neutralizing antibodies was sufficient to protect mice from a challenge with 100 PFU of CHIKV (42).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, natural antibodies present in the sera of uninfected C57BL/6 mice were able to partially inhibit CHIKV (75). Furthermore, therapies based on passively transferred anti-CHIKV neutralizing antibodies conferred protection to A129 mice (42,44,45,70,71,73,(76)(77)(78) and nonhuman primates (37) against CHIKV and protection to mice against more distantly related arthrogenic alphaviruses (43,93,96), establishing the key role of humoral immunity in the control of CHIKV replication. Interestingly, complete protection from CHIKV challenge can be obtained using adoptive transfer of antibodies induced by immunization with a CHIKV/IRES vaccine candidate and occurs in the absence of CD4 ϩ /CD8 ϩ T cells (42); a titer of 35 for neutralizing antibodies was sufficient to protect mice from a challenge with 100 PFU of CHIKV (42).…”
Section: Discussionmentioning
confidence: 98%
“…Antibodies against CHIKV are crucial to control CHIKV infection (37,42,44,45,(70)(71)(72)(73)(74)(75)(76)(77)(78). Thus, to study the ability of MVA-CHIKV to elicit humoral immune responses against CHIKV, we analyzed the levels of CHIKV envelope-specific antibodies present in the sera of C57BL/6 mice immunized with one or two doses of MVA-CHIKV (see Materials and Methods).…”
Section: Mva-wt and Mva-chikv Induce Similar Magnitudes And Polyfunctmentioning
confidence: 99%
“…Thus, it was of importance to assess the individual merits of new CHIKV vaccine platforms in a more stringent animal model that more closely resembles a clinical setting. Antibody responses are known to correlate with protection against CHIKV (29)(30)(31)(32)(33)(34)(35)(36), but CD4 T cell responses may also be important (37)(38)(39). Thus, it was of importance to determine the potential immunological differences that our vaccine candidate might display.…”
Section: Discussionmentioning
confidence: 99%
“…Bindarit, a macrophage chemoattractant protein-1 (MCP-1) inhibitor, ameliorates inflammatory disease in mouse models of RRV and CHIKV, and may be a candidate for treatment of acute disease in humans (Rulli, Guglielmotti et al 2009, Rulli, Rolph et al 2011. Studies of neutralising monoclonal anti-CHIKV antibodies have demonstrated effective attenuation of viraemia and disease in knockout and neonatal mouse models of CHIKV (Couderc, Khandoudi et al 2009, Fric, Bertin-Maghit et al 2013, Pal, Dowd et al 2013). This therapy may prove useful for prevention of peri-natal maternal transfer (Gould, Coutard et al 2010, (Warter, Lee et al 2011, Fric, Bertin-Maghit et al 2013).…”
Section: Treatment Of Chikv Diseasementioning
confidence: 99%
“…Studies of neutralising monoclonal anti-CHIKV antibodies have demonstrated effective attenuation of viraemia and disease in knockout and neonatal mouse models of CHIKV (Couderc, Khandoudi et al 2009, Fric, Bertin-Maghit et al 2013, Pal, Dowd et al 2013). This therapy may prove useful for prevention of peri-natal maternal transfer (Gould, Coutard et al 2010, (Warter, Lee et al 2011, Fric, Bertin-Maghit et al 2013). …”
Section: Treatment Of Chikv Diseasementioning
confidence: 99%